Christian ethics in the face of secularism - Jakobus M. Vorster (Verbum et Ecclesia, 2012)
This article deals with the implications of modern secularism for the concept of Christian ethics. How does the decline of Christianity in modern Western societies impede the validity of a Christian ethical approach to contemporary social issues? The concept secularism is explained. The argument then moves to the meta-theory of Christian ethics, namely the revelation of God as it is expressed in the book of nature, the written word, and the incarnate Word, Jesus Christ. The article concludes that as long as Christian ethics remains faithful to this meta-theory, understands the modern macro-ethical questions and maintains a deep social focus, it will remain relevant in a secular society.